Risk Assessment and Fractionation of Cadmium Contamination in Sediment of Saguling Lake in West Java Indonesia - Dwina Roosmini; Eka Wardhani; Suprihanto Notodarmojo (Journal of Engineering and Technological Sciences, 2022)
This research focused on the speciation and distribution patterns of cadmium in surface sediment from Saguling Lake, which is located in the Upper Citarum River. Organic compounds and heavy metals from anthropogenic activities in the watershed have contaminated the river. Sample from the upper layer of the sediment from Saguling Lake were taken from 12 locations, representing the dry and the rainy seasons in the period 2015-2018. Sediment cadmium (Cd) classification was conducted through a sequential extraction technique to determine Cd’s bioavailability and its risk to the water environment. During the rainy season, the total Cd concentration in the upper layer of the sediment was higher than during the dry season. The average dry and rainy season concentrations were 11.12 ± 2.16 mg/kg and 14.82 ± 1.48 mg/kgm in the sampling locations, distributed differently with the following order of the largest to the smallest concentration: 10B > 1A > 4 > 3 > 2 > 1B > 10A > 7 > 9 > 5 > 6 > 8 for the dry season, and 4 > 1A > 1B > 2 > 7 > 5 > 9 > 3 > 6 > 10A > 8 > 10B for the rainy season. All sampling locations (>60%) showed Cd in the resistant fraction, indicating no significant anthropogenic input of Cd into the surface sediment but more geological input due to high erosion. The values of RAC, ICF, and GFC indicate that the Cd in the surface sediment can be categorized as low risk.